Confrontation Naming and Reading Abilities at Primary School: A Longitudinal Study - Chiara Luoni; Umberto Balottin; Laura Rosana; Enrico Savelli; Silvia Salini; Cristiano Termine (Behavioural Neurology)
Background. Confrontation naming tasks are useful in the assessment of children with learning and language disorders. Objectives. The aims of this study were (1) providing longitudinal data on confrontation naming; (2) investigating the role of socioeconomic status (SES), intelligence, age, and gender in confrontation naming; (3) identifying relationship between confrontation naming and reading abilities (fluency, accuracy, and comprehension). Method. A five-year longitudinal investigation of confrontation naming (i.e., the Boston Naming Test (BNT)) in a nonclinical sample of Italian primary school children was conducted (n=126), testing them at the end of each school year, to assess nonverbal intelligence, confrontation naming, and reading abilities. Results. Performance on the BNT emerged as a function of IQ and SES. Significant correlations between confrontation naming and reading abilities, especially comprehension, were found; BNT scores correlated better with reading fluency than with reading accuracy. Conclusions. The longitudinal data obtained in this study are discussed with regard to reading abilities, intelligence, age, gender, and socioeconomic status.